The role of the city in formation of communicative media - Golodnikova, Yu.A. (Культура народов Причерноморья, 2007)
В статье проводится анализ влияния медиа на восприятие пространства города и исследуется роль города в формировании коммуникационных сред. У статті проводиться аналіз впливу медіа на сприйняття простору міста та досліджується роль міста у формуванні комунікаційних середовищ. The article focuses on revealing the ways of influencing of the media upon the perception of space of the city and the role of the city information of communicative media.